Jaringan Aktor dalam Komunikasi Publik Era Digital pada Kasus Penghinaan Penjual Es Teh oleh Miftah Maulana - Sari Riantika Damayanti (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
A sermon by Miftah Maulana, Special Envoy of the President of the Republic of Indonesia for Religious Harmony and Development of Religious Facilities, who mocked an iced tea vendor named Sunhaji in November 2024, sparked widespread controversy in digital spaces. This study aims to analyze the actor-network formed in this case and examine how digital narratives shape public opinion and pressure. A qualitative approach with a descriptive-analytical case study method was employed. Data were collected through a literature review of journal articles, national media reports, and public discussions on social media. Analysis was conducted using Actor-Network Theory (ANT) and Fisher's Narrative Paradigm. The findings reveal that social media functioned as the primary amplification medium, connecting human actors—Miftah, Sunhaji, and netizens—with non-human actors including viral videos, algorithms, and social norms. The solidarity narrative toward Sunhaji met the criteria of narrative coherence and fidelity, making it widely accepted by the public, while Miftah's clarification failed to generate moral resonance. This case confirms that in the digital era, public communication is not merely the transfer of information but a navigation of complex narrative networks. The theoretical implications reinforce the relevance of ANT and the narrative paradigm in analyzing digital communication phenomena, while emphasizing the importance of digital literacy and communication ethics for public officials.